1989
DOI: 10.1038/jcbfm.1989.53
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate Dehydrogenase Activity in the Rat Cerebral Cortex following Cerebral Ischemia

Abstract: Summary: The effect of cerebral ischemia on the activity of pyruvate dehydrogenase (PDH) enzyme complex (PDHC) was investigated in homogenates of frozen rat cerebral cortex following 15 min of bilateral common ca rotid occlusion ischemia and following 15 min, 60 min, and 6 h of recirculation after 15 min of ischemia. In frozen cortical tissue from the same animals, the levels of labile phosphate compounds, glucose, glycogen, lactate, and pyruvate were determined. In cortex from control ani mals, the rate of [l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
2

Year Published

1990
1990
2009
2009

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 43 publications
2
29
2
Order By: Relevance
“…This study confirms the previously reported post ischemic depression in PDHC activity in normogly cemic animals (Cardell et al, 1989) and extends the observation to 18 h of recovery. In addition, our present results show that PDHC activity was re-…”
Section: Discussionsupporting
confidence: 92%
“…This study confirms the previously reported post ischemic depression in PDHC activity in normogly cemic animals (Cardell et al, 1989) and extends the observation to 18 h of recovery. In addition, our present results show that PDHC activity was re-…”
Section: Discussionsupporting
confidence: 92%
“…However, given our in vitro experiments that show that "active" purified PDHC is targeted and inactivated by peroxynitrite, the most likely mechanism of enzyme inhibition is that PDHC in its active, dephosphorylated form is susceptible to attack and subsequent inactivation by peroxynitrite. In addition, loss of PDHC activity after cerebral ischemia and reperfusion in rat arterial occlusion models is the result of impaired maximal activity rather than covalent inhibition caused by increased protein phosphorylation [21,54].…”
Section: Discussionmentioning
confidence: 99%
“…However, given our in vitro experiments that show that "active" purified PDHC is targeted and inactivated by peroxynitrite, the most likely mechanism of enzyme inhibition is that PDHC in its active, dephosphorylated form is susceptible to attack and subsequent inactivation by peroxynitrite. In addition, loss of PDHC activity after cerebral ischemia and reperfusion in rat arterial occlusion models is the result of impaired maximal activity rather than covalent inhibition caused by increased protein phosphorylation [21,54].The results obtained in vivo suggesting that peroxynitrite mediates postischemic PDHC enzyme inhibition are supported by in vitro experimentation in which incubation of purified PDHC with SIN-1 is associated with decreased PDHC activity and increased 3-nitrotyrosine immunoreactivity The inactivation of PDHC by peroxynitrite, in vitro, is primarily due to tyrosine nitration, although the small protection afforded by DTT indicates that S-nitrosation also contributes to enzyme inhibition (Fig. 6).…”
mentioning
confidence: 99%
“…The inhibition of this enzyme is suggested to occur as a result of free radical mediated protein oxidation and may be potentiated by increased calcium concentrations (Bogaert et al, 1994). Inhibition of the PDHC (to 50% of control levels) takes place as early as 15 min following reperfusion (Cardell et al, 1989) consistent with the occurrence of NADH hyperoxidation following hypoxia (as shown in this study) and ischemia (Feng et al, 1998). Inhibition may, as a result, restrict the supply of reducing equivalents and substrates to mitochondria thereby decreasing aerobic metabolism.…”
Section: Nadh Reduction and Hyperoxidationmentioning
confidence: 99%